Karierna pričakovanja študentov psihologije - Boštjančič, Eva (Psihološka obzorja (Ljubljana), 2011)
Developing career expectations is a process through which young people get to know their own characteristics, skills, and values, assess their opportunities on the labor market, and develop various career plans and goals for themselves. In this study, 190 students completed the "Career Planning" questionnaire, which is composed of a series of open-response questions. The results showed that students have very little work experiences connected with psychology and more in administration, working with children, and volunteer work. They tend to evaluate their skills as high. Their career expectations are distributed by employment area, in which they draw attention to various obstacles in achieving their set goals, especially with regard to personality factors and financing. They primarily expect good interpersonal relations and working conditions from their future workplaces.
Keywords: student; students; študenti; psihologija; psychology; career expectations; kariera; Kariera people; karierna pričakovanja; career planning; načrtovanje kariere